2016
DOI: 10.1128/aem.01850-16
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a Recombination-Proficient Escherichia coli System for Adaptive Laboratory Evolution

Abstract: Adaptive laboratory evolution typically involves the propagation of organisms asexually to select for mutants with the desired phenotypes. However, asexual evolution is prone to competition among beneficial mutations (clonal interference) and the accumulation of hitchhiking and neutral mutations. The benefits of horizontal gene transfer toward overcoming these known disadvantages of asexual evolution were characterized in a strain of Escherichia coli engineered for superior sexual recombination (genderless). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Experimental evolution of HGT in bacteria has been more difficult to study; however, recombination has been incorporated into E. coli experiments using conjugation systems . One of these studies confirmed results in S. cerevisiae that incorporating recombination into an experimental system will speed up adaptation .…”
Section: High‐throughput Methods For Identifying and Tracking Beneficmentioning
confidence: 79%
“…Experimental evolution of HGT in bacteria has been more difficult to study; however, recombination has been incorporated into E. coli experiments using conjugation systems . One of these studies confirmed results in S. cerevisiae that incorporating recombination into an experimental system will speed up adaptation .…”
Section: High‐throughput Methods For Identifying and Tracking Beneficmentioning
confidence: 79%
“…The results in these more complex experimental environments are clear in showing the evolutionary benefits of mixed microbial populations. Accelerated adaptive evolution occurs when bacterial cultures are capable of intercellular DNA exchange In the development of novel yeast strains adapted to stressful fermentation conditions (high temperatures, high ethanol concentrations), interspecific hybrids are the products of selection for the most effective cultures …”
Section: How Should Appreciation Of Multispecies Interactions In Adapmentioning
confidence: 99%
“…r Accelerated adaptive evolution occurs when bacterial cultures are capable of intercellular DNA exchange. 195,196 r In the development of novel yeast strains adapted to stressful fermentation conditions (high temperatures, high ethanol concentrations), interspecific hybrids are the products of selection for the most effective cultures. 197 The accumulating data on introgression and hybridization qqq in eukaryotic species of all kinds (yeasts, plants, animals) make it possible that the majority of adaptive innovations occur in periods of genome restructuring that follow interspecific crosses (see above).…”
Section: How Should Appreciation Of Multispecies Interactions In Adapmentioning
confidence: 99%
“…More generally, studies that expose evolving populations to nutrient-limiting conditions, unusual carbon sources, or stressful environments (e.g. containing antibiotics) tend to show that sexually recombining populations can outperform asexual populations (Zeyl & Bell, 1997;Goddard et al, 2005;Cooper, 2007;Gray & Goddard, 2012;Winkler & Kao, 2012;Peabody et al, 2016). Removal of deleterious alleles may play an important role in such beneficial recombination (Zeyl & Bell, 1997;Cooper, 2007;Peabody et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…containing antibiotics) tend to show that sexually recombining populations can outperform asexual populations (Zeyl & Bell, 1997;Goddard et al, 2005;Cooper, 2007;Gray & Goddard, 2012;Winkler & Kao, 2012;Peabody et al, 2016). Removal of deleterious alleles may play an important role in such beneficial recombination (Zeyl & Bell, 1997;Cooper, 2007;Peabody et al, 2016). Quantitatively and qualitatively different effects of recombination on adaptation in such studies may have various causes, including the kinds of adaptation considered, the number of loci underlying an adaptive trait and the fitness effects of individual mutations.…”
Section: Introductionmentioning
confidence: 99%